2019
DOI: 10.1109/access.2019.2949919
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Software Outsourcing Partnership Formation: An Exploratory Analysis

Abstract: Software Outsourcing Partnership (SOP) is a type of cooperative client-vendor relationship. SOP is an emerging strategy and is different from ordinary software development outsourcing (SDO). Usually, a fruitful outsourcing association might be converted to an outsourcing partnership. Conversely, SOP is not a risk-free business, numerous barriers associated with SOP. The overarching target of this exploratory paper is to find and analyze a list of barriers that are considered obstacles for vendors in the conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 94 publications
(193 reference statements)
0
14
0
Order By: Relevance
“…Vendor financial instability and no relation specific investment can only be affected by poor leadership. Mehta reports that “leadership and team management” requires proper experience to manage and lead teams; sometimes, they adopted improper approaches to motivate their team members. Therefore, poor leadership will result in poor project management.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Vendor financial instability and no relation specific investment can only be affected by poor leadership. Mehta reports that “leadership and team management” requires proper experience to manage and lead teams; sometimes, they adopted improper approaches to motivate their team members. Therefore, poor leadership will result in poor project management.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The Literature review shows that a significant number of studies [11], [12], [13], [14], [15], [16], [17], [18] have focused on various issues of software offshore outsourcing and IT outsourcing. Despite the discussion of the study background in section II, the following paragraph also shows the relevant research work.…”
Section: A Study Motivationmentioning
confidence: 99%
“…Ilyas et al [11] identified success factors of software integration in GSD. Ali et al [12] investigated the barriers that are important for the software outsourcing partnership. Niazi et al [17] conducted a systematic literature review that identifies factors regarding trust in offshore software partnership.…”
Section: A Study Motivationmentioning
confidence: 99%
See 2 more Smart Citations